A novel UGT1 marker associated with better tolerance against irinotecan-induced severe neutropenia in metastatic colorectal cancer patients - Chen, Sylvia (Pharmacogenomics J, 2015)
The risk of severe irinotecan-induced neutropenia has been shown to be related to the UGT1 variant UGT1A1*28, which increases exposure to the potent metabolite SN-38. Our goal was to identify a novel UGT1 marker(s) using 28 haplotype-tagged single nucleotide polymorphisms genotyped by mass spectrometry. By characterizing the UGT1 sequence from a cohort of 167 Canadian metastatic colorectal cancer (mCRC) patients and a validation cohort of 250 Italian mCRC patients, we found rs11563250G, located in the intergenic region downstream of UGT1, to be significantly associated with reduced risk of severe neutropenia (odds ratio (OR)=0.21; p=0.043 and OR=0.27; p=0.036, respectively, and OR=0.31 when combined; p=0.001), which remained significant upon correction for multiple testing in the combined cohort (p=0.041). For the two-marker haplotype rs11563250G and UGT1A1*1 (rs8175347 TA(6)), the OR was of 0.17 (p=0.0004). Genetic testing of this marker may identify patients who might benefit from increased irinotecan dosing.